Comparison of soil properties and Kentucky bluegrass shoots mineral composition prior to and after 10-11 years irrigation with recycled water - Lin, Yuhung, author; Qian, Yaling, advisor; Davis, Jessica, committee member; Klett, James E., committee member; Andales, Allan, committee member (Colorado State University. Libraries, 2016)
In Colorado, fresh water is one of the most valuable and limited natural resources. Due to population growth, an increase of fresh water withdrawal has been reported by U.S. Geological Survey. Irrigation with recycled water has been utilized as a means to alleviate the stress on potable water supplies and facilitate the reuse of treated wastewater. Recycled water irrigation is taking place at landscape sites such as public parks, golf courses, and school playgrounds. Research information is needed to better understand the long-term effects of recycled water irrigation on urban landscapes. Therefore, the objectives of this research were to: 1) assess changes in soil chemical properties after 5 and 11 years of recycled water irrigation, 2) determine if there is any heavy metal accumulation in soil after 11 years of recycled water irrigation, 3) evaluate Kentucky bluegrass (Poa pratensis L.) (KBG) turf quality grown on golf courses irrigated with recycled water, and 4) determine the relationship of turf quality to shoot mineral concentrations and soil chemical properties. To address Objectives 1 and 2, soil samples were collected and analyzed at the commencement (in 2004) and 11 years after recycled water irrigation on three golf courses, 5 metropolitan parks, 1 school ground, and 1 zoo. Samples were taken at 0-20, 20-40, 40-60, 60-80, and 80-100 cm depths on golf courses and at 0-20 and 20-40 cm depths at other locations. Soil was analyzed for texture, soil pH, soil organic matter, soil salinity [soil electrical conductivity (EC)], exchangeable sodium percentage (ESP), cation exchange capacity (CEC), nitrate-N, chloride (Cl), boron (B), and AB-DTPA extracted phosphorus (P), iron (Fe), manganese (Mn), arsenic(As), chromium (Cr), cadmium (Cd), cobalt (Co), nickel (Ni), lead (Pb), zinc (Zn) and copper (Cu). Averaging over all sites, soil pH was 0.25-0.3 higher in 2015 and 2009 than in 2004. The increase was greater at deeper depths. Soil salinity (EC) was 0.84, 0.88, and 0.98 dS m-1in 2004, 2009 and 2015, respectively. The magnitude of increase in ESP after recycled water irrigation indicated potential sodicity problems. Calcium based product applications reduced ESP at soil surface depths. In contrast, significant increase in ESP was found at deeper soil depths. No increase in soil nitrate-N was observed over 5 and 11 years with recycled water irrigation, therefore, leaching of nitrogen to the groundwater was not a great concern. AB-DTPA extracted As, Co, and Ni decreased after 11 years of recycled water irrigation. Soil Cd, Cr, Cu, Pb, and Zn did not show significant change from 2004 to 2015. Results revealed that there was no sign of heavy metal accumulation. To address Objectives 3 and 4, research was conducted on eight golf courses, including three courses in Denver after 10 years of recycled water irrigation, three courses in the nearby cities receiving recycled water for more than 10 years, and two courses receiving fresh surface water for irrigation. Results indicated that Na concentration in KBG shoot tissues increased by 4.3-9.9 times, Cl by 1.5-1.3 times, B by 1.3-3.5 times whereas K/Na ratio was reduced by 74-90%. Multiple regression analysis indicated shoot Na accumulation had the highest association to turf quality decline (R2= 0.65). Soil sodium adsorption ratio (SAR) in 0-20 cm depth was highly associated with KBG shoot Na concentration (R2= 0.70).